Between Bacchae and Bahanalii—balkanizing classical reception. (2nd March 2023) - Todorović, Nebojša
Abstract: This article sets Euripides' Bacchae in dialogue with Goran Stefanovski's Bahanalii, a play that was performed in the immediate aftermath of Yugoslavia's break-up. Contrapuntal reading shows how the two plays problematize conservative epistemologies by imagining their borderlands as privileged sites of knowledge production. Euripides' Bacchae opens with a Dionysus who arrives on stage from a faraway land where Greeks and non-Greeks live mixed together. My reading of this passage challenges Edward Said's interpretation of the Bacchae as a play about the dangers of 'what lies beyond familiar borders'. Instead, the Bacchae performs an exercise in literary imagination in which a border-minded worldview responds to Athens' dwindling geopolitical prestige, resists narratives of Greek exceptionalism inherited in the aftermath of the Persian wars, and foresees a return to a kind of Hellenic balkanization avant la lettre . In Bahanalii, Stefanovski resists idealizing mindsets by staging a contradictory Dionis, one that focalizes the epistemological power of the border, while also embodying the uncanny poltergeist of the violence that plagued Yugoslavia in the 1990s. In juxtaposing the narratives of Yugoslav and ancient Athenian exceptionalism, this comparison unlocks a 'balkanizing' paradigm of classical reception which complements and complicates existing theoretical accounts of classical reception.